Evidence of arbovirus co-infection in suspected febrile malaria and typhoid patients in Nigeria - Baba, Marycelin; Logue, Christopher Hugh; Oderinde, Bamidele; Abdulmaleek, Hauwa; Williams, Joshua; Lewis, James; Laws, Thomas R; Hewson, Roger; Marcello, Alessandro; D' Agaro, Pierlanfranco (The Journal of Infection in Developing Countries, 2013)
Introduction: Clinical symptoms of malaria and typhoid infections are virtually indistinguishable from those initially seen in many arbovirus infections. Here we describe arbovirus co-infection detected in 310 sera samples collected from febrile, clinically suspected malaria/typhoid patients in Borno State, Nigeria. Methodology: Tested initially for Plasmodium falciparum by microscopy and for Salmonella Typhi by Widal test, samples were subsequently tested for chikungunya (CHIKV), yellow fever (YFV), dengue (DENV) and West Nile viruses (WNV) by plaque reduction neutralization test. Results: While 92% of patients tested positive for malaria, typhoid, an arbovirus infection, or a combination of one or more of these types of infections, less than 1% of the patients tested positive for malaria alone and only 3.9% tested positive for typhoid alone. Approximately half of the patients tested positive for infection with a single arbovirus (48%) regardless of the presence or absence of malaria or typhoid. Of those who showed 90% to 95% virus neutralization, 67.7% had neutralizing antibodies against DENV, 50% against CHIKV, 25% against WNV and 8.7% against YFV. Eight per cent tested negative against all six pathogens, suggesting that other arboviruses not tested for in this study may also be circulating in Nigeria. Conclusions: The results suggest that misdiagnosis of arbovirus co-infections as malaria infections, combined with a lack of virus surveillance and underreporting of arbovirus infections, increases the potential for undetected and uncontrolled spread of important vector-borne arboviruses becoming serious underlying public health concerns in Nigeria.